Evaluasi CPPB IRT pada UMKM Cake Lapis Legit di Kota Bandar Lampung - Lianti, Lita; Latifah, Yasmin; Marvie, Ilham (Communication in Food Science and Technology, 2023)
The number of Small Enterprices is increasing and occurs in almost all regions of Indonesia, one of them is in Bandar Lampung City. One of the Small Enterprices in Bandar Lampung City which operates in the food production sector is the Small Enterprice Lapis Legit Cake. To ensure the safety of products distributed by a Small Enterprice, it is necessary to evaluate Good Manufacturing Practices for Home Industry Food Production (CPPB-IRT) and then the results of the evaluation can be used by the Small Enterprice to prepare for SPP-IRT certification so that products can be distributed legally, more widely and increase consumer trust. Data collection was carried out by a direct observation of the object being studied. Data analysis was carried out by comparing the conditions in the field with the CPPB-IRT form based on PERKA BPOM No HK.03.1.23.04.12.2207 of 2012. The evaluation results of the CPPB-IRT requirements showed that in the Small Enterprice Lapis Legit Cake there was 1 major non-conformity, 5 serious non-conformity and 2 critical non-conformities. The results of the IRTP assessment show that the Small Enterprice Lapis Legit Cake is at level IV, so the IRTP must carry out internal audits every day.